Respuesta :

Answer:

x= -3/2

Step-by-step explanation:

((4)²)^x = 1/(4)³

4²^x = 4³

thus the powers are same then

2x =-3

x=-3/2

Answer:

x = - [tex]\frac{3}{2}[/tex]

Step-by-step explanation:

Using the rules of exponents

[tex](a^m)^{n}[/tex] = [tex]a^{mn}[/tex]

[tex]a^{-m}[/tex] ⇔ [tex]\frac{1}{a^m}[/tex]

Note that 16 = 4² and 64 = 4³ , then

[tex]16^{x}[/tex] = [tex]\frac{1}{64}[/tex] , can be expressed as

[tex](4^2)^{x}[/tex] = [tex]\frac{1}{4^3}[/tex] , that is

[tex]4^{2x}[/tex] = [tex]4^{-3}[/tex]

Since the bases on both sides are equal, then equate the exponents

2x = - 3 ( divide both sides by 2 )

x = - [tex]\frac{3}{2}[/tex]